The influence of work discipline and organizational culture on the performance of elementary school teachers in Gaung Anak Serka district - Yeni Karmalia; Fadly Azhar; Daviq Chairilsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This research aims to provide valuable insights for educational policymakers, school principals, and teachers. A deeper understanding of how work discipline and organizational culture influence teacher performance can help direct improvement efforts toward enhancing educational quality. This study examines the effect of work discipline and organizational culture on teacher performance in Gaung Anak Serka district, Indragiri Hilir regency. The research population consisted of 91 teachers, with a randomly selected sample of 75 respondents, determined using Taro Yamane's formula. The data collection process utilized questionnaires measured with a Likert scale. The research employed a descriptive analysis technique, followed by inferential statistical analysis, which included analysis requirement tests and statistical hypothesis testing. The findings demonstrate that work discipline and organizational culture significantly impact teacher performance individually and collectively. Teachers with high work discipline exhibit greater efficiency, responsibility, and commitment to their professional duties. A strong organizational culture fosters a supportive work environment, collaboration, and motivation among teachers, leading to improved performance. The study concludes that enhancing work discipline and cultivating a positive organizational culture are essential strategies for improving teacher effectiveness. These findings highlight the importance of school leadership in fostering these factors to achieve better educational outcomes.